DETERMINATION OF THE COST OF TECHNICAL SUPERVISION SERVICES ON THE PUBLIC ROADS AT ALL STAGES OF THE INVESTMENT PROCESS - Artem Bezuglyi; Ihor Hresko; Olena Belska; Yuliya Bibyk (Дороги і мости, 2022)
Introduction. The process of new construction, reconstruction and overhaul of the roads requires the contractor to comply with all norms and rules established by regulatory documents and the customer of the works. Such functions are entrusted to the customer, or they can be performed by specialists who are engaged to perform technical supervision at the road works facilities. Technical supervision specialists primarily monitor the process of work at the facility, the measures of which provide for the implementation of a complex of actions to check the quality of work and protect the interests of the customer.